Spectral functions in the ϕ4-theory from the spectral Dyson-Schwinger equations - Horak, Jan; Pawlowski, Jan M.; Wink, Nicolas (Physical review, 2020)
We develop a nonperturbative functional framework for computing real-time correlation functions in strongly correlated systems. The framework is based on the spectral representation of correlation functions and dimensional regularization. Therefore, the nonperturbative spectral renormalization setup here respects all symmetries of the theories at hand. In particular, this includes space-time symmetries, as well as internal symmetries such as chiral symmetry, and gauge symmetries. Spectral renormalization can be applied within general functional approaches such as the functional renormalization group, Dyson-Schwinger equations, and two- or n-particle irreducible approaches. As an application, we compute the full, nonperturbative, spectral function of the scalar field in the ϕ4-theory in 2+1 dimensions from spectral Dyson-Schwinger equations. We also compute the s-channel spectral function of the full ϕ4-vertex in this theory.
Im Titel ist die Zahl "4" hochgestellt
Gesehen am 28.01.2021